Scientific Article Publication Training in Reputable International Journals - Christine Dewi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
One of the main criteria of the Tridharma of Higher Education by lecturers is to conduct research and publish the results of their research. The relevance of lecturers conducting investigations, research, and publishing scientific articles is raised substantially by the demands for publication by the higher education community. Referring to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform, academic promotions for lecturers are required to publish their work in accredited national or international scientific journals in their fields. This rule provides direction so that scientific publications and functional positions of Lecturers in Indonesia continue to increase. The ability to publish scientific articles is very important for researchers in Indonesia. Unfortunately, many of them continue to struggle with putting together scientific publications outlining their findings and publishing them in high-quality, peer-reviewed international journals. For this reason, the PKM program in Indonesia publishes scientific articles written by students, professors, and researchers to help them improve their writing skills. There were researchers, professors, and students present from all throughout Indonesia. The seminar's attendees walked away with a wealth of information on publishing their research in high-quality international journals, thanks to this event.